Effects of a Cognitive-Functional Intervention Method on Improving Executive Function and Self-Directed Learning in School-Aged Children with Attention Deficit Hyperactivity Disorder: A Single-Subject Design Study - Mi Ji Kim; Hae Yean Park; Eun-Young Yoo; Jung-Ran Kim (Hindawi-Wiley, 2020)
Background. School-aged children with attention deficit hyperactivity disorder (ADHD) face many difficulties with self-directed learning because of their poor executive function. This leads to secondary problems such as learning disabilities and depression, so the role of intervention to improve executive function in school-aged children with ADHD is important. Objective. The present study is aimed to investigate how cognitive-functional (Cog-Fun) intervention affected executive function of school-aged children with ADHD and the sustainability of these effects. To investigate the effects of changes in the executive function of school-aged children with ADHD through Cog-Fun intervention in self-directed learning. Method. A single-subject A-B-A research design was employed in this study. Three children aged 9-10 years who were diagnosed with ADHD were selected. A total of 17 experimental sessions were conducted. The Cog-Fun intervention program was implemented during the intervention phase. To measure dependent variables, Behavior Rating Inventory of Executive Function (BRIEF) and Homework Problems Checklist (HPC) were used. Significant changes in executive function assessed by the Children's Color Trails Test (CCTT) and Stroop test were analyzed through two-standard deviation band analysis. Additionally, video clips of task performance were analyzed to examine qualitative performance changes in self-directed learning. Result. All three participants presented statistically significant changes with a number of near-misses of CCTT and color words score of Stroop test during the intervention. T-scores of the Global Executive Composite (GEC) decreased after the intervention, indicating improvement in executive function. The follow-up period revealed retention of the improved executive function. Additionally, self-directed learning improved in all participants after the implementation Cog-Fun intervention. Conclusion. The study supports the effectiveness of Cog-Fun intervention in improving executive function in school-aged children with ADHD and confirmed that the improvement of executive function ultimately leads to the improvement of self-directed learning performance.